2020
DOI: 10.3390/cells9071643
|View full text |Cite
|
Sign up to set email alerts
|

The E2F Pathway Score as a Predictive Biomarker of Response to Neoadjuvant Therapy in ER+/HER2− Breast Cancer

Abstract: E2F transcription factors play critical roles in the cell cycle. Therefore, their activity is expected to reflect tumor aggressiveness and responsiveness to therapy. We scored 3905 tumors of nine breast cancer cohorts for this activity based on their gene expression for the Hallmark E2F targets gene set. As expected, tumors with a high score had an increased expression of cell proliferation-related genes. A high score was significantly associated with shorter patient survival, greater MKI67 expression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 102 publications
7
79
0
Order By: Relevance
“…Tumor immune microenvironment has been repeatedly demonstrated to be deeply involved in cancer progression by our group and others [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Recently, antitumor immunity was reported to correlate with increased cell cycle activity in pancreatic cancer [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor immune microenvironment has been repeatedly demonstrated to be deeply involved in cancer progression by our group and others [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Recently, antitumor immunity was reported to correlate with increased cell cycle activity in pancreatic cancer [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average value was used for genes with multiple probes. Gene expression data, which were transformed for log 2 , were used in all analyses as we have previously reported [ 6 , 17 , 36 , 58 , 66 ]. We used published data of Hussain et al (GSE62452; tumor sample; n = 69, adjusted pancreases sample; n = 61) [ 67 ], Chen et al (GSE57495; n = 63) [ 68 ], and Bocklandt et al (GSE28746; tumor sample; n = 45, adjusted pancreases sample; n = 45) [ 69 ] to investigate the association of the G2M pathway scores with patient survival.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that highly proliferative cancers are more likely to respond to cytotoxic chemotherapy [ 9 , 10 , 39 , 40 ]. Given our results that low- ITPKC expression TNBCs are highly proliferative, we hypothesized that they are associated with better NAC response.…”
Section: Resultsmentioning
confidence: 99%
“…TNBC is known to relate to several proliferation-related pathways [ 7 , 8 ]. Our group has previously reported that TNBC has high activity of the E2F pathway [ 9 ] and G2M checkpoint pathway [ 10 ], both of which are essential components of the cell cycle and critical for cell proliferation.…”
Section: Introductionmentioning
confidence: 99%